2007
DOI: 10.1007/s11695-007-9109-z
|View full text |Cite
|
Sign up to set email alerts
|

Intragastric Balloon-Induced Satiety is Not Mediated by Modification in Fasting or Postprandial Plasma Ghrelin Levels in Morbid Obesity

Abstract: BIB induces a temporary sense of satiety in morbidly obese patients which is not mediated by modification of fasting or postprandial levels of plasma ghrelin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 32 publications
0
31
1
6
Order By: Relevance
“…The authors concluded that BIB had its value for the treatment of morbid obesity and in preparing patients for bariatric surgery [31]. Conversely, in a double-blind, randomized study including 21 patients with morbid obesity comparing BIB and sham, showing that the satiety sensation induced by the BIB did not last, and was not related to changes in ghrelin levels, the weight loss at 4 months was identical between BIB and control groups [32].…”
Section: Bioenterics Intragastric Balloon (Bib)mentioning
confidence: 98%
See 1 more Smart Citation
“…The authors concluded that BIB had its value for the treatment of morbid obesity and in preparing patients for bariatric surgery [31]. Conversely, in a double-blind, randomized study including 21 patients with morbid obesity comparing BIB and sham, showing that the satiety sensation induced by the BIB did not last, and was not related to changes in ghrelin levels, the weight loss at 4 months was identical between BIB and control groups [32].…”
Section: Bioenterics Intragastric Balloon (Bib)mentioning
confidence: 98%
“…Les auteurs en concluaient que le BIB avait sa place dans le traitement de l'obésité morbide et dans la préparation des malades à une chirurgie bariatrique [31]. A l'inverse, dans une étude en double aveugle, randomisée, sur 21 malades présentant une obésité morbide, comparant BIB et sham, et montrant que la sensation de satiété induite par la pose de BIB était temporaire, non liée à des modifications du taux de ghréline, la perte pondérale à 4 mois était la même dans le groupe BIB et le groupe contrôle [32].…”
Section: Bioenterics Intragastric Balloon (Bib)unclassified
“…Le ballon intragastrique n'entraîne pas de modification significative des taux sériques de leptine ni de ghréline [3,4].…”
Section: Concept Et Mécanismes D'actionunclassified
“…Au cours d'une étude randomisée en double insu testant l'efficacité du ballon contre un ballon fictif associé à une prise en charge diététique, il faut noter que la perte de poids moyenne dans les deux groupes (12,7 versus 8,9 kg, respectivement) n'était pas significativement différente, pouvant suggérer un effet placebo du ballon [4].…”
Section: Concept Et Mécanismes D'actionunclassified
“…One study reported decreased fasting ghrelin concentrations after a balloon-induced weight loss of 9.4 % [17]. A second study found similar meal-suppressed ghrelin concentrations in a sham-controlled design [18]. A third study noted increased ghrelin values after 1-month of intragastric balloon treatment that normalised to pretreatment levels 3 months after balloon removal [7].…”
Section: Introductionmentioning
confidence: 97%